Designing an Educational Application Based on Passura Toraya Toraja Carvings to Strengthen Cultural Understanding in Elementary Schools - Makawi, Faizal Erlangga; Djirong, Agussalim; Sahnir, Nurachmy (PT Mattawang Mediatama Solution, 2025)
This research focuses on designing an educational application drawing from Passura Toraya Toraja Carvings in Toraja. This Toraja Carvings is crucial in strengthening cultural understanding based on their symbolic meaning embedded in curriculum context in Elementary Schools. In this research, a concept of application design is created to showcase the beauty of Toraja Toraja Carvings. Which can be implemented as a learning tool to support cultural understanding of elementary students. The method of this research is a literature review, by analizing references from Art criticism, Geometry, and Ilustration of Toraja Toraja Carvingss. This research results shows that an educational application with the implementation of Passura Toraya can be applied to education by emphasizing three main points namely; (1) Geometry learning in Arts and Math, both can be applied as a great source of learning in schools; (2) Ilustration of Passura Toraya consists of hundreds of Toraja Carvingss that originally four Toraja Carvingss which later developed as times goes by; (3)Symbolic meaning of Passura Toraya helps understand the meaning of Toraja Culture in Schools. In Designing an educational application, the main crusial aspect of design is creating the core of its application. Therefore, three main objectives are drawn to provide a more comprehensive learning experience in schools integrated with technology. This research does not specifically creating a website, rather designing a concept of a better application for learning in schools.